(untitled) (VERUM: Journal of Scientific Initiation, 2023)
The study of the history of educational institutions has sparked interest from different researchers. In the field of the history of education, using the perspective of cultural history, investigations have highlighted the importance of contextual relationships in understanding the meanings produced in a given space and time. In this sense, authors such as Pesavento (2004) and Gertz (2005) served as theoretical references for this work. Our study aims to analyze and understand the processes of implementation of the São Marcos School Group in its early years of operation, considering that between 1938 and 1947, the institution was known by different names. The methodology used was historical documentary analysis, as argued by Pimentel (2001), requiring the organization of tables based on the selected sources for the study. The set of documents shows that the political context of the Estado Novo, implemented during Getúlio Vargas’ government, played an important role in the organization of everyday practices of the school groups. As a partial result, we highlight that in a regional dimension, in a community of students descended from Italian immigrants, civic-nationalist activities played a significant role in spreading a patriotic sentiment, and the change in the institution’s name is also related to the political context of the period.